Photopolymerization-based synthesis of iron oxide nanoparticle embedded PNIPAM nanogels for biomedical applications - Daniel J. Denmark; Robert H. Hyde; Charlotte Gladney; Manh-Huong Phan; Kirpal S. Bisht; Hariharan Srikanth; Pritish Mukherjee; Sarath Witanachchi (Taylor & Francis Group, 2017)
Conventional therapeutic techniques treat patients by delivering biotherapeutics to the entire body. With targeted delivery, biotherapeutics are transported to the afflicted tissue reducing exposure to healthy tissue. Targeted delivery devices are minimally composed of a stimuli responsive polymer allowing triggered release and magnetic nanoparticles enabling targeting as well as alternating magnetic field (AMF) heating. Although more traditional methods, like emulsion polymerization, have been used to realize such devices, the synthesis is problematic. For example, surfactants preventing agglomeration must be removed from the product increasing time and cost. Ultraviolet (UV) photopolymerization is more efficient and ensures safety by using biocompatible substances. Reactants selected for nanogel fabrication were N-isopropylacrylamide (monomer), methylene bis-acrylamide (crosslinker), and Irgacure 2959 (photoinitiator). The 10 nm superparamagnetic nanoparticles for encapsulation were composed of iron oxide. Herein, a low-cost, scalable, and rapid, custom-built UV photoreactor with in situ, spectroscopic monitoring system is used to observe synthesis. This method also allows in situ encapsulation of the magnetic nanoparticles simplifying the process. Nanogel characterization, performed by transmission electron microscopy, reveals size-tunable nanogel spheres between 40 and 800 nm in diameter. Samples of nanogels encapsulating magnetic nanoparticles were subjected to an AMF and temperature increase was observed indicating triggered release is possible. Results presented here will have a wide range of applications in medical sciences like oncology, gene delivery, cardiology, and endocrinology.